The race relations competence workshop: theory and results - Alderfer, Clayton P; Alderfer, Charleen; Bell, Ella Louise; Jones, Jimmy (Human Relations, 1992)
This paper presents the theoretical basis and the associated perceptions of race relations that characterized a race relations competence workshop which served as the educational component of an overall program to improve race relations among managers within the fictitiously named XYZ Corporation. Workshop activities combined didactic and experiential methods and focused on group and individual levels of learning based on embedded intergroup relations theory. An assessment of the race relations competence workshop was carried out as part of an overall effort to evaluate the race relations improvement program in the company. Employing measures of both global evaluation and perceptions of race relations among managers, the study showed that Blacks evaluated the workshop more favorably than Whites, that reports of having information about the workshop were positively associated with favorable evaluations of the workshop, that workshop participants more than nonparticipants were likely to perceive Whites as hurting Blacks and less likely to perceive Blacks as hurting Whites. Additional analyses showed that, while the workshop generally had favorable effects for participants, the groups most likely to show unfavorable consequences were White male first level managers younger than 41 years and White female first level managers older than 40 years.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/126-048-778-075-671 tex.type: [object Object]
Keywords: dept.mft; race relations competence workshop